Protein phosphorylation in plant immunity: insights into the regulation of pattern recognition receptor-mediated signaling - Park, Chang-Jin; Caddell, Daniel F.; Ronald, Pamela C. (Frontiers in Plant Science, 2012)
Plants are continuously challenged by pathogens including viruses, bacteria, and fungi. The plant immune system recognizes invading pathogens and responds by activating an immune response. These responses occur rapidly and often involve post-translational modifications (PTMs) within the proteome. Protein phosphorylation is a common and intensively studied form of these PTMs and regulates many plant processes including plant growth, development, and immunity. Most well-characterized pattern recognition receptors (PRRs), including Xanthomonas resistance 21 (XA21), flagellin sensitive 2 (FLS2), and elongation factor (EF)-Tu receptor (EFR), possess intrinsic protein kinase activity and regulate downstream signaling through phosphorylation events. Here, we focus on the phosphorylation events of plant PRRs that play important roles in the immune response. We also discuss the role of phosphorylation in regulating mitogen-associated protein kinase (MAPK) cascades and transcription factors in plant immune signaling.